(untitled) (Journal of Educational Sciences, 2022)
A high level of anxiety in children of primary school age with hearing disorders affects their communicative and emotional sphere, reduces motivation for learning and development. The article defines the phenomenon of aggressiveness. The signs and causes of aggression of children with hearing impairments in primary school are presented. The methods of psychological and pedagogical treatment that correct the aggressive behavior of primary school children with hearing impairments are introduced. The concepts of sand therapy, relaxation and art therapy are revealed. The possibilities of game therapy in working with younger schoolchildren are explained. Diagnostic research methods, such as the observation method, the "Self-portrait" method by A.Karelin, the "Hand testing” method by E. Wagner, Benevolskaya’s questionnaire for teachers were performed. The performance of a teacher-psychologist in schools with inclusive experience include 4 areas: advisory, diagnostic, informational-educational and developmental. The article also defines the necessity and effectiveness of psychological and pedagogical correctional work in order to reduce aggressiveness in children with hearing impairments. The program of psychological and pedagogical correction of aggressive behavior in younger schoolchildren was proposed, edited and tested by authors of the article. Reduction in the aggressiveness of younger schoolchildren with hearing impairments who took participation in experiment confirmed the effectiveness of the program, which allows it to be used by modern psychologists and teachers in inclusive education. Key words: inclusive education, students with hearing impairment, children with special needs in learning, child aggressiveness, psychological and pedagogical correction.